2012
DOI: 10.1055/s-0032-1321502
|View full text |Cite
|
Sign up to set email alerts
|

The Relative Proportion of Preterm Births Complicated by Premature Rupture of Membranes in Multifetal Gestations: A Population-Based Study

Abstract: Preterm birth is a profound public health issue. Despite a decrease in the mortality rate after extremely preterm birth, the morbidity is increasing. 1 Preterm births contribute to 75% of all perinatal mortality and more than half the long-term morbidity in infant survivors. 2 It has been estimated that $30 to 35% of preterm births are medically indicated, 40 to 45% are attributed to spontaneous preterm labor, and 25 to 30% follow preterm premature rupture of membranes (PROM). 3 Based on U.S. birth records, Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…A total of 745 physicians were excluded because they were aged ≥60 years ( n  = 158), or because data on working hours during their first pregnancy ( n  = 528) or pregnancy complications ( n  = 40) were not available. Additionally, because women with multiple conceptions (a situation in which two or more fetuses are conceived at the same time in the same woman) are more likely to experience adverse pregnancy complications, including preterm birth (PTB) or bleeding [14], the majority of previous studies restricted their sample to women with singleton pregnancies. Thus, we also excluded women with multiple conceptions ( n  = 19).…”
Section: Methodsmentioning
confidence: 99%
“…A total of 745 physicians were excluded because they were aged ≥60 years ( n  = 158), or because data on working hours during their first pregnancy ( n  = 528) or pregnancy complications ( n  = 40) were not available. Additionally, because women with multiple conceptions (a situation in which two or more fetuses are conceived at the same time in the same woman) are more likely to experience adverse pregnancy complications, including preterm birth (PTB) or bleeding [14], the majority of previous studies restricted their sample to women with singleton pregnancies. Thus, we also excluded women with multiple conceptions ( n  = 19).…”
Section: Methodsmentioning
confidence: 99%
“…1 PPROM is defined as rupture of the fetal membranes prior to 37 weeks gestation and prior to the onset of labor. The frequency of PPROM is higher in multi-fetal gestations, 2,3 with one study reporting this complication in 11% of twins, 19% of triplets, and 20% of quadruplets. 3 Pakrashi et al reported that PPROM also occurs at an earlier gestational age among multiple gestations with 36% of twin PPROM, 28% of triplet PPROM, and 50% of quadruplet PPROM occurring at < 28 weeks.…”
Section: Introductionmentioning
confidence: 99%
“…3 Pakrashi et al reported that PPROM also occurs at an earlier gestational age among multiple gestations with 36% of twin PPROM, 28% of triplet PPROM, and 50% of quadruplet PPROM occurring at < 28 weeks. 3 …”
Section: Introductionmentioning
confidence: 99%
“…According to their results, quadruplet pregnancies are more likely to be diagnosed with preterm premature rupture of the membranes (10.64% compared to 9.61% for triplets and 6.17% for twin pregnancies, p < 0.001). In another retrospective cohort study of more than 290,000 live births, premature rupture of the membranes complicated 19.6% for quadruplet and 100% for higher order (>4) pregnancies compared to 19.3% for triplets, 11.2% for twins, and 3.1% for singletons [79]. In the same study, the proportion of preterm birth attributable to premature rupture of the membranes for extremely preterm gestational ages (before 28 weeks of pregnancy) was 50% for quadruplets and 100% for higher order pregnancies compared to 26.9, 34.6, and 26.5% for triplets, twins, and singletons, respectively (p < 0.001).…”
Section: Complications and Management Of Quadruplet/quintuplet Pregnamentioning
confidence: 98%